An Advisory Centre on International Investment Law: Is perfect the enemy of good? - Charlie Garnjana-Goonchorn (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
This Perspective explores the benefits that an Advisory Centre on International Investment Law (ACIIL) would bring to developing countries and the upcoming challenges. The author then argues that the kick-start of a "less than perfect" ACIIL now would sow the seeds for a more full-scale ACIIL in the future.
Keywords: 330